The concept of mimesis in Adorno and Benjamin - Gagnebin, Jeanne-Marie (Universidade Estadual Paulista / UNESP, 2007)
The concept of mimesis is presented through Plato, Arístótle, Adorno, Horkheimer and Benjamin. The differences between Adorno and Benjamin are stressed. Adorno's final thought lead us to consider an old platonic assertation the experience of the true knowledge, that is, the union between Eros and Logos.